Pengaruh Label Halal, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Ms Glow (Studi Kasus Pada Mahasiswa FEB Angkatan 2019 Universitas Islam Malang) - Syauqina Hanifah; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of halal label variables, brand image and product quality on purchasing decisions for Ms Glow's skincare products. This research used a case study on FEB students class of 2019 at the Islamic University of Malang who were selected by accidental sampling.Determination of the number of samples using the Malhotra formula and the results obtained were 60 respondents. Data collection was carried out using a questionnaire. The data analysis method used in this study is Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Statistical Test (t test), and Coefficient of Determination Test (Adjusted R2) and the process of analysis using SPSS 21. The results of the study stated that the variable halal label and brand image had no effect on purchasing decisions, while product quality had an effect on purchasing decisions. Keywords: Halal Label, Brand Image, Product Quality, Purchase Decision